Phase formation and microstructure of gamma irradiated Bi-2223 Superconductor - Mohiju Z.; Adnan N.A.; Hamid N.A.; Abdullah Y. (Institute of Physics Publishing, 2023)
Gamma rays; Hydraulic machinery; Microstructure; Phase structure; Scanning electron microscopy; Solid state reactions; Superconducting materials; X ray diffraction; Bi-2223 superconductors; Gamma irradiation; Grain microstructure; Hydraulic press machines; Irradiated samples; Solid state reaction method; Structure characterization; Superconducting phase; Irradiation